Factors associated with formal volunteering among retirees - Jongenelis, Michelle; Dana, Liyuwork Mitiku; Warburton, J.; Jackson, B.; Newton, R.U.; Talati, Zenobia; Pettigrew, Simone (SPRINGER, 2020)
The present study developed and tested a comprehensive multivariate model designed to assess the relative importance of various factors found or proposed in previous research to be associated with engagement in volunteering among 799 fully retired Australian older adults (62% female; mean age = 71.92 years (SD = 6.69)). Engagement in volunteering in the 12 months preceding the study and a range of sociodemographic, psychological, physical, social, and attitudinal variables were measured. Respondents’ perceived personal responsibility to volunteer was found to be especially important in the tested model. This variable was directly associated with engagement in volunteering and acted as an important mediator between the following variables and volunteering engagement: personal growth, social connectedness, religious attendance, self-rated health, and depression. Efforts to increase volunteering engagement among older adults may therefore need to target perceptions of their responsibility to volunteer. Especially important focus areas for future strategies may include increasing social connectedness, facilitating personal growth, and improving self-rated health.